2020
DOI: 10.1186/s12888-020-02885-6
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and validity of PHQ-9 in patients with major depressive disorder in psychiatric hospital

Abstract: Background To assess the reliability and validity of Patient Health Questionnaire-9 (PHQ-9) for patients with major depressive disorder (MDD) and to assess the feasibility of its use in psychiatric hospitals in China. Methods One hundred nine outpatients or inpatients with MDD who qualified the Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM-IV) criteria completed PHQ-9 and Hamilton Depression Scale (HAMD-1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(120 citation statements)
references
References 33 publications
8
91
0
Order By: Relevance
“…In fact, this scale was considered by a recent study as the best tool for evaluating the results reported by patients with depression [39]. In addition, unlike other depression scales, the PHQ-9 includes nine items that are based on the Diagnostic and Statistics Manual for Mental Disorders, 4th Edition (DSM-IV) [41].…”
Section: Diagnostic Assessmentmentioning
confidence: 99%
“…In fact, this scale was considered by a recent study as the best tool for evaluating the results reported by patients with depression [39]. In addition, unlike other depression scales, the PHQ-9 includes nine items that are based on the Diagnostic and Statistics Manual for Mental Disorders, 4th Edition (DSM-IV) [41].…”
Section: Diagnostic Assessmentmentioning
confidence: 99%
“…This is incompatible with previous results of several other national published studies [23 -33]. Thus, recent systematic reviews and metaanalysis indicated that the prevalence of depression among medical students worldwide was around 30% [24][25][26][27]. In another study carried out in Vietnam by Quynh et al…”
Section: Discussionmentioning
confidence: 60%
“…The total scores determine the severity of stress. It can be interpreted as mild stress up to 6, moderate stress from 7 to 12 and severe stress from 13 to 18 [26]. The study protocol was submitted to the University ethics committee (15/2019) for ethical approval.…”
Section: Methodsmentioning
confidence: 99%
“…At the screening visit, measures of alcohol problem severity (e.g., hazardous and harmful alcohol use) and tonic craving levels were collected via the AUDIT [ 24 ] and Penn Alcohol Craving Scale (PACS; [ 29 ]), respectively. To measure participants’ degree of depressive and generalized anxiety symptomatology, well-validated mental health surveys, the Patient Health Questionnaire (PHQ-9) [ 30 , 31 ] and Generalized Anxiety Disorder 7-Item Scale (GAD-7) [ 32 , 33 ] were administered.…”
Section: Methodsmentioning
confidence: 99%